Health care huddles. Issue 1 (January 2015) - Provost, Shannon M.; Lanham, Holly J.; Leykum, Luci K.; McDaniel, Reuben R.; Pugh, Jacqueline
<x xml:space="preserve">Abstract</x> Background: Health care huddles are increasingly employed in a range of formats but theoretical mechanisms underlying huddles remain relatively uncharted. Purpose: A complexity science view implies that essential managerial strategies for high-performing health care organizations include meaningful conversations, enhanced relationships, and a learning culture. These three dimensions informed our approach to studying huddles. We explore new theories for how and why huddles have been useful in health care organizations. Methods: We used a study design incorporating literature review, direct observation, and semistructured interviews. A complexity science framework guided data collection in three health care settings; we also incorporated theories on high-reliability organizations to analyze our observations and interpret huddle participants' perspectives. Findings: We identify theoretical paths that could link huddles to improvement in patient safety outcomes. Huddles create time and space for conversations, enhance relationships, and strengthen a culture of safety. Huddles can be of particular value to health care organizations seeking or sustaining high reliability. Practice Implications: Achieving high reliability, the organizational capacity to deliver what is intended to be delivered every time is difficult in complex systems. Managers have potential to create conditions from which huddle outcomes that support high reliability are more likely to emerge. Huddles support efforts to improve patient safety when they afford opportunities for heedful interactions to take place among individuals caring for patients and embed mindfulness into the organization.